Serum very-long-chain fatty acids levels determined by gas chromatography in the diagnosis of peroxisomal disorders in Poland - Stradomska, Teresa Joanna; Tylki-Szymańska, Anna (Folia Neuropathologica, 2009)
Peroxisomal disorders are a large group of genetically determined metabolic diseases in which the biogenesis of peroxisomes is defective or there is a deficiency of only a single enzyme activity or substrate transporter. The objective of this report is to present ten years of experience in the diagnostics of peroxisomal disorders in Poland. Very-long-chain fatty acid (VLCFA) levels as a biomarker for peroxisomal defects were determined by gas chromatography in 1264 subjects with suspicion of peroxisome disease. Peroxisome biogenesis disorders (PBD) were diagnosed in 8 patients, bifunctional protein deficiency in 3 and X-linked adrenoleukodystrophy (X-ALD/AMN) in 127 hemi- or heterozygotes. The frequency of PBD was estimated as 0.20 : 100 000, and that of X-ALD/AMN 2.9 : 100 000 in Poland. Mean total delay time (onset of symptoms and diagnosis) for X-ALD/AMN was 2.2 years (range 0.25-13). High correlation of serum C26:0 concentration and survival for PBD patient (r2 = 0.822; p < 0.001) was found.